Types of Complications and Associated Factors in Patients Undergoing Permanent Cardiac Pacemaker Implantation: A Systematic Review - Sugiharto F; Asmara AD; Sari WP; Freitas LA; Ramdani D; Anna A; Nuraeni A; Trisyani Y; Purnomo Y (Journal of Multidisciplinary Healthcare)
Firman Sugiharto,1 A Danang Asmara,1 Wulan Puspita Sari,1 Lurdes Acorta Freitas,1 Dadan Ramdani,1 Anastasia Anna,2 Aan Nuraeni,2 Yanny Trisyani,2 Yudi Purnomo3 1Master Study Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Critical Care and Emergency Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 3Nursing Department, Hasan Sadikin General Hospital, Bandung, West Jawa, IndonesiaCorrespondence: Anastasia Anna, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21 hegarmanah, Jatinangor, Sumedang, West Java, Indonesia, Tel +6282130109989, Fax +62 02287793411, Email anastasia.anna@unpad.ac.idBackground: Permanent Pacemaker (PPM) implantation is essential in treating cardiac arrhythmias and conduction disorders, especially in patients with heart failure. Although PPM has been proven to improve quality of life and prolong life expectancy in patients with cardiac conduction disorders, post implantation complications still often occur.Purpose: This study aimed to identify types of complications and associated predictors in patients undergoing PPM implantation.Methods: This review used a systematic review design and follows the guidelines of the Cochrane Handbook for Systematic Reviews and the Preferred Reporting Item for Systematic Reviews and Meta-analysis (PRISMA). The database used was PubMed, CINAHL: Medline Ultimate, ScienceDirect, Scopus, and search engines: Google Scholar. Articles with observational designs and RCTs in English were included without limitation of publication year.Results: This review analyzed 15 articles. The analysis showed that there are five categories of factors which influences the incidence of complications in patients after PPM implantation: demographic, pre-existing clinical, comorbid disease, procedural, operator experience, and activity factors. The complications that are most frequently reported are generator erosion, pacemaker infection, pneumothorax, atrial lead displacement, battery depletion, and even death after PPM implantation.Conclusion: There are many incidents of complications and factors that influence complications in patients after PPM placement. The reported complications underscore the importance of careful patient selection and procedure execution to minimize risks. Healthcare providers should emphasize patients with risk factors to provide targeted monitoring and management. Integrating a multidisciplinary approach involving cardiologists, nephrologists, surgeons, and the nursing team is essential to optimizing patient care and improving clinical outcomes.Keywords: complication, heart failure, permanent pacemaker, predictors